Effect of water management in soil on weed interference in the onion cultivation system - Souza, Matheus de Freitas (Universidade Federal Rural do Semi-Árido, 2019)
Agricultural practices function as an ecological filter of weeds, selecting those more adapted to the agro-system. The characteristics of the weed species and the disturbances promoted by crops shape the weed community, influencing the productive performance of the crops. Among the practices, irrigation can directly affect the establishment of some weed species, and a better-adapted community can intensify the degree of interference on the crop. This study aims to evaluate the changes caused by two irrigation systems (high and low water application rate) in the weed community over three onion crop cultivars (Allium cepa L.), and how these changes affect productivity, water use and system interference period. The γ, α, β-diversity were altered by onion cultivation over the three years of cultivation. The system with higher water supply (micro-sprinkler) favored the diversity and weed richness, mainly in the second year of cultivation compared to the system with water restriction (drip). The dominant weed species in the first crop cycle changed compared to the last cycle for both irrigation systems. The change in the weed community between the years of cultivation affected the commercial bulb productivity and water use efficiency of onion cultivated under drip and micro-sprinkler. For drip irrigated onion crops, the reduction in water use efficiency is even more drastic. The relative yield of the onion was influenced by the duration of the coexistence period or weed free, irrespective of the irrigation systems. Growing periods of weed interference significantly reduced onion production in all years. In the drip system, the critical period of prevention (PCPI) ranged from 25 to 36 DAE in 2016, 12 to 28 DAE in 2017 and 16 to 89 DAE in 2018 based on the 5% level of acceptable yield loss. In the micro-sprinkler system the PCPI ranged from 06 to 24 DAE in 2016, 10 to 62 DAE in 2017 and 24 to 65 DAE in 2018. The duration of the PCPI depends on the irrigation system used and the composition of the weed community. Irrigation systems influence the beginning and end of PCPI. Weeds reduce the sustainability of the irrigated onion cultivation system when they are not controlled
Keywords: Dominância; Drip; Interferência; Micro-sprinkler; Dominance; Drip; Interference; micro-sprinkler; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA